A review and insights on Poynting vector theory and periodic averaged electric energy transport theories. (February 2015) - Calamaro, N.; Beck, Y.; Shmilovitz, D.
Abstract: Electric energy transport theory is one of the key factors in smart grid development. Electric energy and power transport theories enable the development of advanced energy metering, improve fault-location algorithms, electric network diagnostics algorithms, power conditioning of active filters and of smart grids, energy storage management at energy reservoirs, and new energy forecasting analytical algorithms. In this paper, the periodic averaged theories, including the periodic averaged formulation of Poynting vector theory, are presented. The presentation is conducted in a unique comparative formalism and approach, enabling the demonstration of equivalence between the various theories in general and the equivalence of some elements in the decomposition of the electrical expressions for the powers in particular. The paper shows the equivalence of the modern theory of Currents׳ Physical Components to the Conservative Power Theory, and its formulation, for being applicable to various grid monitoring and energy control applications. A corrected computation for the reactive power by means of time-domain Conservative Power Theory is proposed as well. Moreover, equivalence in single phase systems between Buchholz apparent power and geometric apparent power is shown, which indicate the suitability of using apparent power definitions to grid manufacturing and modern distribution systems design.